Russia's catch-all nuclear rhetoric in its war against Ukraine: A balancing act between deterrence, dissuasion, and compellence strategies - Liviu Horovitz; Anna Clara Arndt (Stiftung Wissenschaft und Politik (SWP), 2022)
A close reading of Russia's nuclear statements and actions during the first seven months of its war against Ukraine reveals a threefold approach. Moscow is walking a fine line between a well-crafted and successful deterrence strategy to prevent foreign military intervention; a more modest and rather unsuccessful attempt at dissuading foreign aid to Ukraine and sanctions against Russia; and incremental nuclear coercion against Kyiv that spurred Western deterrence messaging in response. This analysis reveals a careful Russian approach, suggesting that cost-benefit calculations are likely to continue to render nuclear escalation unlikely. However, nuclear use cannot be fully discounted, particularly if war-related developments severely imperil the survival of Russia's regime.
Keywords: 320; Russia; invasion of Ukraine; nuclear deterrence; nuclear weapons; dissuasion; compellence; NATO; United States; military intervention; sanctions